2018
DOI: 10.1007/s00125-018-4743-7
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of beta cell acetyl-CoA carboxylase-1 in mice impairs insulin secretion and beta cell mass

Abstract: Aims/hypothesisPancreatic beta cells secrete insulin to maintain glucose homeostasis, and beta cell failure is a hallmark of type 2 diabetes. Glucose triggers insulin secretion in beta cells via oxidative mitochondrial pathways. However, it also feeds mitochondrial anaplerotic pathways, driving citrate export and cytosolic malonyl-CoA production by the acetyl-CoA carboxylase 1 (ACC1) enzyme. This pathway has been proposed as an alternative glucose-sensing mechanism, supported mainly by in vitro data. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…Unfortunately, they measured these variables at a concentration of glucose where secretion was unchanged (20 mmol/l) and they did not show under their experimental condition that high glucose itself was able to inhibit fat oxidation, as anticipated. Interestingly, this study reported a novel role of ACC1 related to the control of beta cell mass prior to adulthood [60].…”
Section: Genetic Studiesmentioning
confidence: 74%
See 1 more Smart Citation
“…Unfortunately, they measured these variables at a concentration of glucose where secretion was unchanged (20 mmol/l) and they did not show under their experimental condition that high glucose itself was able to inhibit fat oxidation, as anticipated. Interestingly, this study reported a novel role of ACC1 related to the control of beta cell mass prior to adulthood [60].…”
Section: Genetic Studiesmentioning
confidence: 74%
“…Acc1-knockout and -knockin mice A recent study employing beta cell-specific Acc1 (also known as Acaca)-knockout mice demonstrated that ACC1 is critical for GSIS [60]. Interestingly, ex vivo islet studies showed that the reduced secretion occurs at low and intermediate glucose concentrations and that the inhibitory effect was overridden at high (20 mmol/l) glucose.…”
Section: Genetic Studiesmentioning
confidence: 99%
“…Moreover, there is also concern that RIP‐Cre may affect GSIS in mice. Some studies indeed showed that RIP‐Cre showed impaired glucose tolerance and GSIS because some transgenic lines using Ins2 and PDX1 promoter fragments triggered Cre expression not only in islet β cells, but also in the brain . However, other researches also showed that RIP‐Cre does not affect gene express in the hypothalamus and other tissues .…”
Section: Discussionmentioning
confidence: 99%
“…1). 26,38 It has been proposed that malonyl-CoA impacts GSIS in beta cells by its well-known function as a suppressor of carnitine palmitoyl transferase 1 (CPT1). 36,37 In beta cells, a function of malonyl-CoA appears to be integrated into the regulation of GSIS; beta cellspecific knockout of ACC1 impairs insulin secretion both in vivo and in vitro.…”
Section: Intracellular Lipid Metabolites As Regulators Of Insulin Secmentioning
confidence: 99%
“…36,37 In beta cells, a function of malonyl-CoA appears to be integrated into the regulation of GSIS; beta cellspecific knockout of ACC1 impairs insulin secretion both in vivo and in vitro. 26,38 It has been proposed that malonyl-CoA impacts GSIS in beta cells by its well-known function as a suppressor of carnitine palmitoyl transferase 1 (CPT1). Metabolic labeling of beta cells has confirmed that fatty acid oxidation is reduced upon glucose loading in beta cells, and blockade of beta-oxidation by etomoxir (CPT1 inhibitor) does not impair GSIS, indicating that beta-oxidation does not provide energy source for GSIS.…”
Section: Intracellular Lipid Metabolites As Regulators Of Insulin Secmentioning
confidence: 99%